Effects of the COVID-19 pandemic on essential health and nutrition service utilisations in Ghana: interrupted time-series analyses from 2016 to 2020. Issue 1 (23rd January 2023) - Kawakatsu, Yoshito; Osei, Ivy; Debpuur, Cornelius; Ayi, Atsu; Osei-Sarpong, Felix; Shetye, Mrunal; Aiga, Hirotsugu; Augusto, Orvalho; Wagenaar, Bradley
Abstract : Objectives: This study aimed to assess the national-level and subnational-level effects of the COVID-19 pandemic on essential health and nutrition service utilisation in Ghana. Design: Interrupted time-series. Setting and participants: This study used facility-level data of 7950 governmental and non-governmental health facilities in Ghana between January 2016 and November 2020. Outcome measures: As the essential health and nutrition services, we selected antenatal care (ANC); institutional births, postnatal care (PNC); first and third pentavalent vaccination; measles vaccination; vitamin A supplementations (VAS); and general outpatient care. We performed segmented mixed effects linear models for each service with consideration for data clustering, seasonality and autocorrelation. Losses of patient visits for essential health and nutrition services due to the COVID-19 pandemic were estimated as outcome measures. Results: In April 2020, as an immediate effect of the COVID-19 pandemic, the number of patients for all the services decreased except first pentavalent vaccine. While some services (ie, institutional birth, PNC, third pentavalent and measles vaccination) recovered by November 2020, ANC, VAS and outpatient services had not recovered to prepandemic levels. The total number of lost outpatient visits in Ghana was estimated to be 3 480 292 (95% CI: −3 510 820 to −3 449 676), followed by VAS (−180 419, 95% CI: −182 658 to −177 956) and ANC (−87 481, 95% CI: −93 644 to −81 063). The Greater Accra region was the most affected region by COVID-19, where four out of eight essential services were significantly disrupted. Conclusion: COVID-19 pandemic disrupted the majority of essential healthcare services in Ghana, three of which had not recovered to prepandemic levels by November 2020. Millions of outpatient visits and essential ANC visits were lost. Furthermore, the immediate and long-term impacts of the COVID-19 pandemic on service utilisation varied by service type and region.